2022
DOI: 10.1039/d2tb01498j
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation therapies for improved wound healing: current trends and technologies

Abstract: Degree of oxygenation is one of the important parameters governing various processes, including cell proliferation, angiogenesis, extracellular matrix production, and even combating the microbial burden at the wound site, all...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…In addition to dissolved oxygen levels, real-time monitoring of ROS formation and distribution in living tissues is another aspect that should not be neglected. 105 Specifically, reactive species include reactive oxygen and nitrogen species (RONS), which are a class of highly reactive molecules produced in living systems, generally as metabolic byproducts and cell signaling molecules. Among them, hydrogen peroxide is considered a relatively stable non-radical species that often acts as a secondary messenger at lower levels and participates in normal life activities and even in tissue repair processes.…”
Section: Monitoring and Sensing Of Oxygen And Reactive Oxygen Speciesmentioning
confidence: 99%
“…In addition to dissolved oxygen levels, real-time monitoring of ROS formation and distribution in living tissues is another aspect that should not be neglected. 105 Specifically, reactive species include reactive oxygen and nitrogen species (RONS), which are a class of highly reactive molecules produced in living systems, generally as metabolic byproducts and cell signaling molecules. Among them, hydrogen peroxide is considered a relatively stable non-radical species that often acts as a secondary messenger at lower levels and participates in normal life activities and even in tissue repair processes.…”
Section: Monitoring and Sensing Of Oxygen And Reactive Oxygen Speciesmentioning
confidence: 99%
“…Wound healing is a well-synchronized dynamic process that requires sufficient energy for various cellular applications such as cell migration, proliferation, ECM production, re-epithelization, and angiogenesis [ 27 ]. Oxygen delivery becomes crucial for meeting the energy demands of the cellular processes, as oxygen supply is limited to a depth of 3–4 mm below the tissue, and a hypoxic condition can delay wound healing [ 28 ]. To enhance wound healing, researchers are actively studying the integration of controlled and sustained oxygen release systems into treatment approaches [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen delivery becomes crucial for meeting the energy demands of the cellular processes, as oxygen supply is limited to a depth of 3–4 mm below the tissue, and a hypoxic condition can delay wound healing [ 28 ]. To enhance wound healing, researchers are actively studying the integration of controlled and sustained oxygen release systems into treatment approaches [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. One promising approach is the use of catalase-based oxygen-generating delivery systems, which take advantage of their abundant release during the wound healing process [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 It has been demonstrated that O 2 delivery to a wound site can accelerate cell proliferation and collagen synthesis, thus promoting tissue regeneration. [5][6][7] Therefore, the design and fabrication of a wound dressing with antibacterial and anti-inflammatory characteristics while supplying adequate oxygen are of vital importance for wound treatments. 8,9 Wound dressings have been developed as an important means of wound repair.…”
Section: Introductionmentioning
confidence: 99%